Eco-Custodians: A Contemporary Analysis of Tree Species Composition and Regeneration Health in Ramsagar and Singra National Parks, Bangladesh - Hossan, Md. Sahadat; Ali, Md. Manik; Bari, Md. Shafiqul; Sarmin, Israt Jahan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
This study systematically assessed tree species composition and regeneration status within two protected national parks in Bangladesh: Singra National Park and Ramsagar National Park. We employed a stratified random quadrat method across 100 sample plots (50 quadrats from each national park of 10 m x 10 m). Our findings revealed 45 tree species belonging to 25 families. Myrtaceae and Dipterocarpaceae were the most dominant family, having a maximum number of species. We identified 16 exotic species of 10 families and 29 native species of 19 families. Phytosociological parameters like density, frequency, abundance, and importance value index (IVI) were determined. Shorea robusta with an IVI of 47.38 dominated Singra National Park, while Eucalyptus camaldulensis with an IVI of 22.67 was most important in Ramsagar National Park. Regeneration status was good for 15.56% of species, fair for 24.44%, poor for 28.89%, and absent for 17.78%. This study implied the need for collaborative conservation strategies involving policymakers, conservationists, and local communities to ensure the parks’ sustainable eco-custodianship. Keywords: biodiversity, conservation, forest, national park, regeneration